Challenges and Risk Factors in Directly Observed Treatment of Tuberculosis in Paraíba: An Epidemiological and Correlational Study - Francisco Patricio de Andrade Júnior; Rayanne Santos Alves; Ana Karina Holanda Leite Maia; Raífe Marcolino Nunes; Nayana da Rocha Oliveira; Eglyn Gustavo Oliveira Melo Melo; Ana Emília Alcântara de Avelar; Andrea Moreira dos Santos; Maria Izabel Cavalcanti da Silva Barros; Jonathan Cordeiro de Morais (REVISTA CEREUS, 2025)
The present study aimed to characterize the clinical-epidemiological profile and risk factors of patients undergoing Directly Observed Treatment (DOT) in the state of Paraíba. This is an epidemiological, quantitative, and descriptive study that used secondary data from the Notifiable Diseases Information System (SINAN). Simple and relative frequencies were calculated, and the Chi-Square Test of Independence, adjusted residuals, and Spearman's bivariate correlation were applied. Between 2019 and 2023, 1,491 patients underwent DOT. The epidemiological profile consisted mainly of men (69.6%), individuals aged 20 to 39 years (39.5%), mixed-race individuals (69.4%), and those with low educational attainment (36.8%). A positive association was found between male patients aged 20 to 59 years and female patients aged 60 years and older (p<0.001). Furthermore, an association was observed between not undergoing DOT and male sex (p=0.030), the presence of HIV (p<0.001) and AIDS (p<0.001), alcoholism (p=0.017), and smoking (p<0.001). Clinically, the pulmonary form was the most prevalent (86.9%). Additionally, the study suggests that a higher number of healthcare facilities is associated with a lower treatment dropout rate (ρ = -0.443, p = 0.009). Given this scenario, it is essential to strengthen public policies that expand access to DOT.